Total and added sugar intakes, sugar types, and cancer risk: results from the prospective NutriNet-Santé cohort. Issue 5 (16th September 2020) - Debras, Charlotte; Chazelas, Eloi; Srour, Bernard; Kesse-Guyot, Emmanuelle; Julia, Chantal; Zelek, Laurent; Agaësse, Cédric; Druesne-Pecollo, Nathalie; Galan, Pilar; Hercberg, Serge; Latino-Martel, Paule; Deschasaux, Mélanie; et al.
ABSTRACT: Background: Excessive sugar intake is now recognized as a key risk factor for obesity, type 2 diabetes, and cardiovascular diseases. In contrast, evidence on the sugar–cancer link is less consistent. Experimental data suggest that sugars could play a role in cancer etiology through obesity but also through inflammatory and oxidative mechanisms and insulin resistance, even in the absence of weight gain. Objective: The objective was to study the associations between total and added sugar intake and cancer risk (overall, breast, and prostate), taking into account sugar types and sources. Methods: In total, 101, 279 participants aged >18 y (median age, 40.8 y) from the French NutriNet-Santé prospective cohort study (2009–2019) were included (median follow-up time, 5.9 y). Sugar intake was assessed using repeated and validated 24-h dietary records, designed to register participants' usual consumption for >3500 food and beverage items. Associations between sugar intake and cancer risk were assessed by Cox proportional hazard models adjusted for known risk factors (sociodemographic, anthropometric, lifestyle, medical history, and nutritional factors). Results: Total sugar intake was associated with higher overall cancer risk ( n  = 2503 cases; HR for quartile 4 compared with quartile 1: 1.17; 95% CI: 1.00, 1.37; P trend  = 0.02). Breast cancer risks were increased ( n  = 783 cases; HRQ4vs.Q1  = 1.51; 95% CI: 1.14, 2.00; P trend  = 0.0007). Results remained significant when weight gain during follow-up was adjusted for. In addition, significant associations with cancer risk were also observed for added sugars, free sugars, sucrose,  sugars from milk-based desserts, dairy products, and sugary drinks ( P trend  ≤ 0.01). Conclusions: These results suggest that sugars may represent a modifiable risk factor for cancer prevention (breast in particular), contributing to the current debate on the implementation of sugar taxation, marketing regulation, and other sugar-related policies. This trial was registered at clinicaltrials.gov as NCT03335644.